Genetic structure and genetic diversity of Swietenia macrophylla (Meliaceae): implications for sustainable forest management in Mexico - Alcala, R.E.; Salazar, H.; Gutiérrez Granados, G.; Snook, Laura K. (2014)
The genetic structure and genetic diversity of Mexican populations of Swietenia macrophylla were evaluated. In Mexico, this neotropical tree reaches its northernmost distribution limit. The relationship between genetic diversity and geographic position (longitude, latitude) of four populations was described. The mean genetic and pairwise genetic differentiations were estimated to study the geographic pattern in the genetic structure. The mean overall values for observed heterozygosis (Ho), expected heterozygosis (He) and fixation coefficient (Fis) were 0.41, 0.71 and 0.449 respectively. The mean values per population of Ho, He and Fis correlated with latitude only. The genetic differentiation between populations revealed by the coefficient of differentiation (Fst= 0.047) was statistically significant (p=0.0001). Unweighted pair group method analysis showed that the extent of pairwise genetic differentiation increased with latitudinal position of populations, although no isolation by distance was observed (r=0.76, p=0.15). Results were discussed in the context of the marginal distribution of Mexican populations. Implications of the results on the conservation of S. macrophylla , particularly for populations located in the Mayan zone were discussed.